THE IMMERSION OF ACRYLIC RESIN WITH INJECTION MOULDING TECHNIQUE ON LOOSE DENTURES DIMENSIONAL CHANGE - Kusdarjanti, Endang; L., Mia Laksmi; Setyowati, Okti (Faculty of Vocational Studies, Universitas Airlangga, 2019)
Background: Acrylic resin is the most commonly used denture base material. One disadvantage is that it can absorb water that can cause changes in dimensions. Changes in the dimensions of acrylic resin are influenced by processing acrylic resin. At present injection molding techniques are known to be better than compression molding. Dimension changes due to water absorption occur in the first 7 days and interval intervals of up to 12 days. Purpose: this study was to determine whether immersion of acrylic resin with Injection molding techniques had an effect on changes in dimensions. Method: The study was conducted on acrylic resin test rods with a size of 25 mm x 25 mm x 5 mm. by using injection molding techniques. Acrylic resins are immersed in water for 24 hours, 48 hours and 12 days. Changes in dimensions are measured using a caliper with an accuracy of 0.01 mm. Statistical analysis was performed using the normality test, homogeneity test, and ANOVA test. Result: this study found that there was no change in dimensions of acrylic resin with water-immersed injection molding techniques 24 hours, 48 hours and 12 days. Conclusion: That immersion of acrylic resin in water at 24 hours, 48 hours, and 12 days with injection molding techniques did not affect changes in dimensions.